PRINCIPAL COURSE OF RESTRUCTURING OF MOTHER AND CHILD HEALTH PROTECTION SERVICE IN MEGAPOLIS - Yu.A. Shcherbuk; A.A. Baranov; A.E. Simakhodskiy; L.V. Erman (Вопросы современной педиатрии, 2008)
The results of structural modification in pediatric and obstetric services were described in this work. This modification was directed to the increase of a quality of medical care to women and children and to the realization of priority national project «health».Key words: restructuring, children, pregnant women, infant mortality.